Estudio de prefactibilidad para la producción y comercialización de cobayos cavia porcellus en la parroquia Guanazán cantón Zaruma - Sánchez Romero, Oscar Esteban (2011)
This feasibility study work has its fulfillment in the parish Guanazán, Canton Zaruma (specifically between Canton Chilla and the parish Guanazán Chilla), is located southeast of the province of El Oro. The objectives of this study:As we have the general objective "To increase the production and marketing of guinea pigs (Cavia porcellus), assessing the financial and technical feasibility of a guinea pig farm, developing a system of semi-tech production" that contributes to bid guinea pig meat in areas where low, using guinea pigs selected lines (improved), and specific objectives: "Analyze the market and consumption of guinea pig meat in the Parish Guanazán and neighborhoods" and "Determining the economic and financial profitability of the production system".The area for this study was between 700 and 1000 m2. Were used 45 guinea pigs (40 females and 5 males), as well as kits to be born during the execution of the study. Guinea pigs were used for type I (short, straight hair), which were placed in pools by stratified and random. The market for this product consists of community events surrounding the place of production, and typical food businesses such as restaurants and hotels, where it has an exclusive market, because the price of this dish is high.This work was 478 export quality guinea pigs, with an average weight of 0.7 kg during the first year, in a total area of 1000 m2 of corrals and remaining kikuyo and other crops. The TIR (Internal Rate of Return) of 39% calculated for the first six years of the project, indicates that for every dollar (USD) spent that dollar will recover and also get a profit of $ 0,39.The capital recovery time will be from the first year, however, is from the second year that the project maintains a positive net flow. In summary, this profitable business plan to compare the TIR generated (39%) with the opportunity cost of capital (banking) that is between 7 and 12% in the best case, there is a margin of 20% difference between both values.